Istota dobrobytu ekonomicznego w socjalizmie - Romanow, Zbigniew (Wydział Prawa i Administracji UAM, 1973)
Economic welfare identified with a comparative maximum of provision for the society needs us dependent on the size of the (generated and verified national income and on its rate of growth as well as on the right distribution of the income for the members of the society. Thus the essence of economic welfare resolves itself into the quantity and quality of goods and services put at the disposal of the society. Unlike the pre-socialist formations, the relation between the goal of all-economic activities and economic welfare of the society is direct, since it expresses concurrence of the natural goal of production and the goal of all-economic activities. Realization of the natural goal of socialist economy follows from the collective ownership of means of production. Economic plans aiming at better satisfaction of the growing requirements of the society constitute the outward form. Realization of the natural goal in socialist economy manifests itself in the direct economic calculus which supplies ways to pick out new lines in making basic means of production in accordance with all-social preferences and to achieve an equilibrium in economy and therefore determines material results of reproduction to a considerable degree. A number of essential economic problems and first of all the mechanism of innovation, the response to economic phenomena and the verification of economic results are not satisfactorily solved by the sphere of allocation decision planning and choosing methods of manufacturing basic means of production with help of direct economic calculus. Therefore it is necessary to stimulate the producer in the field of choice of manufacture metods (within the scope of autonomous decisions at the central level) and accomplishment of economic tasks in accordance with all-social interest and in this connection to use the market economic calculus, besides the direct economic calculus, what is linked with financial interest in the results of work. As utility effects are superior to value effects, commodity — and — money categories and market mechanism are regarded as instruments of prompt accomplishment of current economic tasks. The limited commodity — and — money fetishism in socialism does not mean handling these categories at will. When parameters of economic calculus are not true, they cannot be a basis for estimation and valuation of the results of economic units' activities. The existence of commodity — and — money categories in socialism does not mean a sovereign operation of market mechanism and law of value. The principle of the central plan superiority is independent of parametric or non — parametric methods of executing that plan.
Essence of Economic Welfare in Socialism